The use of Panax notoginseng saponins injections after intravenous thrombolysis in acute ischemic stroke: a systematic review and meta-analysis - Yaoyuan Liu; Yaoyuan Liu; Yaoyuan Liu; Puyu Niu; Hongchang Ji; Zhe Chen; Zhe Chen; Jingbo Zhai; Xinyao Jin; Xinyao Jin; Bo Pang; Bo Pang; et al. (Frontiers Media S.A., 2024)
BackgroundAs a bioactive metabolite preparation widely used in acute ischemic stroke (AIS), the efficacy and safety of Panax notoginseng saponins injections (PNSI) in patients with AIS after intravenous thrombolysis remain to be evaluated.MethodsThis study included randomized controlled trials published before 26 April 2024 in 8 databases. AIS patients who received intravenous thrombolysis were included. The control group receiving conventional treatment and the treatment group receiving additional PNSI. Primary outcomes were selected as mortality, disability, and adverse events. Secondary outcomes were selected as all-cause mortality, improvement of neurological deficit, quality of life, and cerebral injury indicators. The revised Cochrane Risk of Bias tool was used to assess risk of bias. Risk ratio (RR) and mean differences (MD) were calculated for binary variables and continuous variables, respectively, based on a 95% confidence interval (CI).ResultsA total of 20 trials involving 1,856 participants were included. None of them reported mortality or disability. There was no significant difference in the adverse events [RR: 1.04; 95% CI: 0.60 to 1.81] and hemorrhagic transformation [RR: 0.99; 95% CI: 0.36 to 2.70] between the two groups. Compared to the control group, the treatment group had a better effect in neurological improvement assessed by National Institutes of Health Stroke Scale [MD: −2.91; 95% CI: −4.76 to −1.06], a better effect in activities of daily living changes in Barthel Index [MD: 9.37; 95% CI: 1.86 to 16.88], and a lower serum neuron-specific enolase level [MD: −2.08; 95% CI: −2.67 to −1.49].ConclusionFor AIS patients undergoing intravenous thrombolysis, the use of PNSI improved neurological deficits and enhanced activity of daily living in the short term without increasing the occurrence rate of adverse events. However, due to the moderate to very low certainty of evidence, it is advisable to conduct high-quality clinical trials to validate the findings of this study.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=466851, Identifier CRD42023466851